Postpartum Depression Screening: A Review for Psychiatrists. Issue 3 (May 2016) - Smith, Erin K.; Gopalan, Priya; Glance, Jody B.; Azzam, Pierre N.
Abstract : Learning Objectives: After participating in this activity, learners should be better able to: Evaluate the rationale for screening women for postpartum depression Assess tools for screening for postpartum depression Objective: To perform a qualitative literature review on screening for postpartum depression (PPD), as applicable to the general psychiatrist. Results are classified by instrument, timing, and clinical setting of the screen. Data sources: A literature search was conducted using the PubMed database for English-language articles published since January 1987. Of the 2406 citations initially identified, 61 articles remained after application of inclusion and exclusion criteria. Results: Among numerous screening tools for PPD, the Edinburgh Postnatal Depression Scale is the most widely used. Data suggest that screening for PPD should commence soon after delivery, with subsequent screens at multiple time-points in the postpartum period. Primary care, pediatric, and obstetric settings are all viable locations for screening, but are ineffective without follow-up mental health evaluations. Less data are available to define optimal patterns either for screening in psychiatric settings or for the psychiatrist's role in managing perinatal depression. Conclusions: The American Congress of Obstetricians and Gynecologists, American Academy of Pediatrics, and most authors firmly recommend screening for PPD. The Edinburgh Postnatal Depression Scale can be administered in various clinical settings. Screening should occur at multiple time-points throughout the first postpartum year. The psychiatrist's role in early detection and prevention of PPD requires further exploration.